(untitled) (International journal of artificial intelligence, 2025)
This article discusses the need to adequately prepare and educate the younger generation for the rapidly developing era, to instill in them the concept of modernity, the characteristics of humanity in their minds, and to effectively use innovations and pedagogical techniques in education.